2002
DOI: 10.1210/jc.2002-020575
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Induces Phosphodiesterase 4B2 Expression in Human Myometrial Cells through a Prostaglandin E2- and Cyclic Adenosine 3′,5′-Monophosphate-Dependent Pathway

Abstract: Intrauterine infections are important etiological factors of preterm labor. They trigger an increase in proinflammatory cytokines, in particular IL-1beta, that induces a cascade of events resulting in the production of potent effectors of myometrial contractility, such as the prostaglandin E(2) (PGE(2)). Within the smooth muscle cells, contractility is under the control of cAMP content, partly regulated by cAMP-phosphodiesterase 4 (PDE4), the predominant family of PDEs expressed in human myometrium. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In this context, several reports have identified marked changes in PDE4 expression during changes in cellular phenotype. Thus, colleagues (Mehats et al, 1999, 2001;Oger et al, 2002) have reported that marked changes in PDE4 variant expression occurs at parturition and that this event correlates with reduced effectiveness of several pharmacological agents used to limit preterm labor. Likewise, Shepherd et al (2004) recently described a profound change in PDE4D isoform expression during differentiation of monocytes into macrophages that may account for differential effects of PDE4 inhibitors between these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several reports have identified marked changes in PDE4 expression during changes in cellular phenotype. Thus, colleagues (Mehats et al, 1999, 2001;Oger et al, 2002) have reported that marked changes in PDE4 variant expression occurs at parturition and that this event correlates with reduced effectiveness of several pharmacological agents used to limit preterm labor. Likewise, Shepherd et al (2004) recently described a profound change in PDE4D isoform expression during differentiation of monocytes into macrophages that may account for differential effects of PDE4 inhibitors between these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β enhance myometrial contractility via different pathways, promoting basal and store-operated calcium entry (Tribe 2002), upregulating TrpC expression (calcium entry channels; Dalrymple et al 2004) and increasing the expression of selected phosphodiesterases, enzymes involved in the control of intracellular levels of cyclic nucleotides (Oger et al 2002). TNF-α reduces the expression of Galphas, the component of the G-protein receptor complex that links to adenylyl cyclase and which increases intracellular cAMP levels promoting myometrial relaxation (Chapman et al 2005).…”
Section: Myometrial Contractilitymentioning
confidence: 99%
“…For example, myocytes pre-incubated with IL1B display greater increases in intracellular calcium (which itself is linked to smooth muscle contraction) in response to stimuli compared with myocytes incubated in control media (Tribe et al 2003). IL1B also increases expression of COX2 (itself an initiator of myometrial contractions; Rauk & Chiao 2000) and phosphodiesterase activity in myocytes (Oger et al 2002) again stimulating contractions. Additionally, IL1B administration stimulates preterm labour in a mouse model (Romero & Tartakovsky 1992).…”
Section: Labourmentioning
confidence: 99%